Pri mojih durih čaka smrt. Osupljiva privlačnost niča. Dekadentne tendence v poeziji Vide Jeraj - Jensterle Doležal, Alenka (Slavia Centralis, 2020)
Next to my Door the Death is waiting. Longing for Love. Longing for Death. Vida Jeraj – Slovenian decadent Poetess The topics of the article are the decadent tendencies in the poetry and life of the first Slovenian female lyricist Vida Jeraj (Franica Vovk, 1875–1932) who was a vital part of the Slovenian modernist network ("Slovenian moderna") in Bled (Zasip) and Vienna. She began to write in the context of transformation in Central European cultures which ended with the collapse of the former joint State. Jeraj belonged to the generation of young cosmopolitan women writers who broke through in in the Fin-de-Siècle period in Slovene society, at that time the periphery of the Austro-Hungarian Empire. In her literary work we analyse poems expressing motives of death.